Comparison of the prognostic values of the 2010 WHO classification, AJCC 7th edition, and ENETS classification of gastric neuroendocrine tumors. Issue 30 (July 2016) - Kim, Beom Su; Park, Young Soo; Yook, Jeong Hwan; Kim, Byung-Sik
Abstract : Abstract: The ability of the European Neuroendocrine Tumor Society (ENETS) system, 2010 World Health Organization (WHO) grading system, and American Joint Committee on Cancer (AJCC) staging system to predict survival after gastric neuroendocrine tumor (NET) resection has not yet been validated. We retrospectively evaluated 175 gastric NETs from 1996 to 2014. WHO grade 3 (G3) patients (n = 66) had a lower survival rate than grade 1 (G1) (n = 39) or grade 2 (G2) (n = 13) patients, with similar high survival rates for G1 and G2 patients. G3 patients had a lower survival rate than mixed-type patients (n = 57). Using the AJCC classification, most of the G1/2 NETs (86.6%) were confined to T1/T2, N0 tumor, and stage I/IIa, but the survival rate was not well distributed. In contrast, G3/mixed tumors were well distributed in terms of T, N, stage, and survival. Using the ENETS classification, 64.6% of the tumors were T2 and only 8.6% were T3. In addition, 49.7% were stage IIIb and only 1.9% was IIa, with poor survival distribution. Our findings strongly suggested that the WHO and ENETS classification systems have shown a low prognostic value. The AJCC TNM system showed a low prognostic value for well-differentiated NETs (G1 or G2). In contrast, the AJCC TNM system had a high prognostic value for G3 or mixed tumors.